PERBEDAAN PENGARUH SWISS BALL EXERCISE DENGAN PILATES EXERCISE UNTUK MENGURANGI LEMAK PERUT PADA PEREMPUAN USIA 25 – 40 TAHUN - Titin Kartiyani; Susanti Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
On each decade age over 25 years old body loss approximately 4 % of the active cells inmetabolism. Young woman has double precentage of fat than young man, are 25 % and 12,5% offat. Estrogen play a role in belly fat accumulation. Women with menstrual cycle disorders have1,89 times greater of obesity risk than women with normal of nutritional status. When it isexpressed in the precentage of body weight, woman has twice more of fat. There are variousexercise techniques such as Swiss Ball exercise and Pilates exercise to reduce belly fat. Thepurpose of this study was to determine the difference effect among Swiss Ball exercise and Pilatesexercise to belly fat in women between 25years to 40 years old. This study reserch used quasrexperimental designwith pre test and post test design. This experiment was performed duringeightweeks. The result of this experiment is know that there is difference effect among Swiss Ballexercise and Pilates exercise to reduce belly fat in women with the significant value 0,000 < 0.05and Piltes has bettereffect than Swiss Ball exercise to belly fat in women with history of deliverybaby